Optimism alongside new challenges: using a rehabilitation framework to explore experiences of a qualitative longitudinal cohort of people living with HIV on antiretroviral treatment in Lusaka, Zambia. Issue 3 (4th March 2018) - Nixon, Stephanie A.; Bond, Virginia; Solomon, Patricia; Cameron, Cathy; Mwamba, Chanda; Hanass-Hancock, Jill; Maimbolwa, Margaret C.; Menon, J. Anitha; Simwaba, Phillimon; Sinyinza, Robert; Siwale, Margaret; Tattle, Stephen; et al.
ABSTRACT: Previous research has demonstrated increased comorbidities related to the chronic effects of HIV. Rehabilitation science offers a useful approach for studying chronic illness. This longitudinal qualitative study used a rehabilitation science approach to explore the experiences over time of women and men living with HIV and on antiretroviral therapy (ART) in the high HIV-prevalence setting of Lusaka, Zambia. Thirty-five participants participated in a total of 99 in-depth interviews from 2012 to 2015. The central pattern that emerged across the participants' narratives was the paradoxical experience of profound optimism alongside significant new challenges. Participants' stories of hopefulness in the face of ongoing struggles played out in three interconnected themes: (1) impacts on my body and life; (2) interventions I am grateful to have and new interventions I need; and (3) stigma reduced and created by ART. Results reflected the ups and downs of life with HIV as a chronic illness. Participants, whilst committed to and healthier on ART, typically experienced multiple physical, psychological and sensory impairments that varied in type, severity and trajectory. Participants valued improved relationships enabled by ART, but yearned for support for living long-term with HIV. Frequently participants reflected that their needs were overlooked related to managing side-effects, exercise, family planning and healthy sexuality. ART strengthened acceptance by self and others through improved health and productivity and through becoming a source of support for others. However, being on ART also led to stigma, driven by persistent associations with sickness, death, lack of productivity and uncertainty. This study points to shortcomings in the current focus of HIV care in Zambia and the region, which centres on initiating and adhering to ART. Findings call for evolution of the HIV care continuum to embrace a more holistic and long-term approach to living with HIV as a chronic and episodic condition.